Analisis Perbandingan Kinerja pada Perguruan Tinggi Perguruan Tinggi yang Beralih Status (Studi Kasus pada Universitas Singaperbangsa Karawang) - Kholida Atiyatul Maula; Suhono suhono (Accounthink, 2018)
This study aims to analyze the differences before and after University status changes to the performance of the University of Singaperbangsa Karawang. This research is a quantitative research. using data collection techniques using observation, interviews and questionnaires distributed to students of the 2012  class who are still active. The results of the study found that there were differences before and after the college switched status and The college should improve the quality of service and improve timeliness and improve performance through training conducted by all employees and lecturers in order to improve educational skills in accordance with the field of work. Then, lecturers are expected to be able to improve and carry out activities in accordance with the aim of creating graduates quality such as increasing research publications, and service community so that they can conduct higher quality teaching. In addition the lecturers are also expected to be able to make the effectiveness of teaching methods and curriculum that are appropriate to the needs of the job market. and the government is expected to help to equip facilities and infrastructure to comply with Dikti standards.